Sleep disturbances in orthopaedic trauma patients. Issue 4 (December 2019) - Lu, Keyin; Barron, John O.; Israel, Heidi; Cannada, Lisa K.
Abstract: Objectives: To determine the prevalence of sleep disturbances in orthopaedic trauma patients 3 months following surgery and to identify any subset(s) of patients at high risk for prolonged sleep disturbance. Design: Prospective cohort. Setting: Level 1 Trauma Center. Patient/Participants: All patients at an orthopaedic trauma clinic from May 3, 2016 to Feb 23, 2017. Main outcome measurements: Baseline patient Pittsburgh Sleep Questionnaire (PSQI) and Insomnia Severity Index (ISI) scores compared to PSQI and ISI scores 3-months postoperatively. Both gender and age stratified data analyses were performed. Results: Sixty-six patients met our inclusion criteria and completed both baseline and 3-month surveys. There were 44 males and 22 females. There was a significant increase in PSQI and ISI scores from baseline to 3 months across all patients. Further analysis revealed significant increases from baseline to 3 months in both PSQI and ISI scores for female patients but not male patients. There was a significant difference from baseline to 3 months in patients 50 years old and under but not for patients above 50 years old. No patients required revision surgery in the first 3 months. Conclusions: More than half of all patients reported continued sleep disturbance 3 months postoperatively. Females are at particularly increased risk for sleep disturbance. These findings demonstrate that sleep disturbances merit attention in the early stages of the postoperative recovery process. Level of evidence: Therapeutic Level II.